UNUSUAL SCINTIGRAPHIC FINDING IN A PATIENT WITH AMIDOARONE-INDUCED THYROTOXICOSIS: A CASE REPORT - Jankulovska, Anamarija; Miladinova, Daniela (Journal of Morphological Sciences, 2021)
Amiodarone, an antiarrhythmic drug with 37% iodine of its weight, is often used for treatment of severe cardiac arrhythmias. Enormous iodine content and structural similarity to thyroxine leads to thyroid dysfunction in 14-18% of patients. A 64-year-old man presented at our department with signs of thyrotoxicosis for further work up. He reported taking amiodarone for treatment of atrial fibrillation for two years. The patient denied any thyroid dysfunctions in the past. Full thyroid examination revealed elevated FT4 and suppressed TSH, with undetectable level of thyroid antibodies, increased iodine urinary concentration and normal thyroid ultrasound features. Although the above mentioned was indicative for amiodarone-induced thyrotoxicosis (AIT) type 2, 99mTc-pertechnetate scan showed normal thyroid uptake, highly unusual for iodine contamination and destructive thyroiditis. We presumed that this was a mixed form of AIT. Amiodarone administration was stopped and the patient was put on antithyroid drug therapy with thiamazole. During the follow up period he became clinically and biochemically euthyroid and thiamazole was discontinued. Thyroid screening should be performed in all patients undergoing amiodarone treatment. The presented case highlights the challenge of differentiation and management of a form of AIT with mixed features of both types.   Keywords : iodine excess, amiodarone induced thyrotoxicosis, mixed form   https://doi.org/10.55302/JMS2143014j